The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s13369-012-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Performance of RC Members Externally Strengthened by FRP Exposed to Different Environments

Abstract: Environmental conditions in the Gulf region are considered to be very aggressive to most structures. The main objective of the paper is to study the performance of RC elements (beams and slabs) strengthened by externally bonded FRP using carbon fiber-reinforced polymer (CFRP) sheets and strips and exposed to different environmental conditions. Six exposure conditions were used in the investigation to represent the Gulf region various environments. The exposure conditions used are laboratory, site, high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Because retrofitting applications often integrate FRP systems into the external face of weakened structures, FRPs are usually exposed to open and potentially harsh environments (Al-Tamimi et al 2015;El-Dieb et al 2012;El-Hassan and El Maaddawy 2019). Temperature exposure is of particular interest because the utilized polymeric materials generally exhibit strong temperature dependence through their mechanical properties with limited temperature increases (approximately 25°C-75°C) (Hawileh et al 2009(Hawileh et al , 2015a and significant so ft ening beyond their glass transition temperature (T g ) (60°C-110°C) (Ou et al 2016;Reis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because retrofitting applications often integrate FRP systems into the external face of weakened structures, FRPs are usually exposed to open and potentially harsh environments (Al-Tamimi et al 2015;El-Dieb et al 2012;El-Hassan and El Maaddawy 2019). Temperature exposure is of particular interest because the utilized polymeric materials generally exhibit strong temperature dependence through their mechanical properties with limited temperature increases (approximately 25°C-75°C) (Hawileh et al 2009(Hawileh et al , 2015a and significant so ft ening beyond their glass transition temperature (T g ) (60°C-110°C) (Ou et al 2016;Reis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While specimen preconditioning in an environmental chamber before loading has been the traditional approach utilized by many researchers, [85][86][87][88][89] it has been shown that such an approach underestimates the deterioration of FRP-concrete under hygrothermal conditioning. Ren et al 90 coupled FTs with a dead load to study the durability of beams (in flexure) subjected to FT-cycles under a sustained load.…”
Section: Studies On Large-scale Frp-concrete Structural Elementsmentioning
confidence: 99%
“…In terms of the failure modes, salt fog cycles and immersion in salt water were associated with failure at the interface of concrete and adhesive, differing from failure in the concrete near-surface substrate of the reference beams, regardless of types of strengthening materials. EI-Dieb et al (2012) conducted research on the long-term (6 and 18 months) performance of reinforced concrete beams and slabs externally strengthened by CFRP exposed to sea water or sabkha soil condition. For the sea water exposure, the specimens were exposed to cycles of immersion in the sea water for 2 weeks followed by 2 weeks of natural drying.…”
Section: Introductionmentioning
confidence: 99%